139k views
4 votes
Solve for y,if 3+3y=1–13y

User AstrOne
by
4.8k points

1 Answer

2 votes

Step 1: Simplify both sides of the equation.

3+3y=1−13y−9

3+3y=1+−13y+−9

3y+3=(−13y)+(1+−9)(Combine Like Terms)

3y+3=−13y+−8

3y+3=−13y−8

Step 2: Add 13y to both sides.

3y+3+13y=−13y−8+13y

16y+3=−8

Step 3: Subtract 3 from both sides.

16y+3−3=−8−3

16y=−11

Step 4: Divide both sides by 16.

16y

16=−11/16

y=−11/16

Answer:

y=−11/16

User Sigma
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.